Ministerial Decree No. 304/2014 On Cancelling Decree No. 393/2008 And Continuing Applying Decree No. 84/2004 Concerning the Commitment of Service and Maintenance Centers for Durable Commodities to Obtain Their Serviceability Approval Certificates from the Industrial Control Administration Before Starting Their Activity And Amending Some Provisions Thereof / translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
The Ministry of Trade, Industry and Investment Decree No. 304 of the Year 2014 – وزارة التجارة والصناعة والاستثمار قرار رقم 304 لسنة 2014